Pediatric Orbital Floor Reconstruction with Split Corticocancellous Rib Graft. (June 2021) - Niklinska, Eva; Pontell, Matthew E.; Jaeger, Nolan; Golinko, Michael; Kelly, Kevin
Background: Orbital floor fractures constitute roughly 20% of all pediatric facial fractures. Reconstructive techniques are broadly subdivided into alloplastic and autologous. While pediatric literature exists for alloplastic orbital reconstruction, autologous orbital reconstruction studies are limited. Here we present several cases of posttraumatic pediatric orbital reconstruction utilizing autologous split rib graft.Methods: After IRB approval, a retrospective chart review was conducted at Monroe Carell Jr. Children's Hospital at Vanderbilt from 2003 to 2019. A review of relevant published literature was also performed.Results: From 2003 to 2019, 5 pediatric patients underwent orbital reconstruction with split rib graft. Of the 5 patients, 3 were female and 2 were male with an age range of 4 to 8 years old (mean 4.8). Two patients had isolated orbital blow-out fractures while 3 presented with concurrent midfacial fractures. In each patient, the orbit was reconstructed by contoured split rib corticocancellous graft. Average length of stay was 5.2 days. There were no postoperative pneumothoraces. Mean follow-up length was 18.7 months, with no rib donor site complications. Each patient had adequate orbital volume restoration with no postoperative globe malposition or persistent diplopia.Conclusion: Pediatric orbital fractures are complex and challenging injuries. While alloplastic reconstruction is common and reliable, the risks of foreign body implantation and fixation must be carefully considered in patients who have not yet reached skeletal maturity. This is especially pertinent in younger patients as orbital growth continues until approximately 9 years of age. Rib graft use for adult orbital reconstruction has been explored. Data in the pediatric literature has not been identified. Corticocancellous rib graft harvest mandates a second surgical site; however, it is relatively inconspicuous with low postoperative morbidity. Corticocancellous rib grafting is a safe and durable option for orbital reconstruction and should be considered for use in the pediatric patient with a growing facial skeleton.